Relationship Of Length - Weight Bigeye Tuna (Thunnus obesus Lowe, 1839) in Indian Ocean - Grin Tommy Panggabean; Siti Nurkhotini; Yonvitner Yonvitner (Departement of Aquatic Resources Management, Faculty of Fisheries and Marine Sciences, IPB University, 2020)
The potential of fisheries resources in Indonesia is 9,931 million tons per year, with the highest potential being in WPP 718 of 1,992 million tons / year (20%), in WPP of 1,228 million / year (12%) and in WPP 711 of 1,143 million tons / year (12%). Bigeye Tuna (Thunnus obesus) is one of the leading commodities from the fisheries sub-sector which is commonly consumed both locally and export. Cilacap Ocean Fishery Port (PPS), Cilacap Regency, is one of the Bigeye Tuna (Thunnus obesus) fish landings caught from the Indian Ocean. This study aims to find out information on the long-term weight ties of Bigeye Tuna (Thunnus obesus) captured from the Indian Ocean and landed at PPS Cilacap, Central Java. According to Cilacap PPS (2014), Bigeye Tuna (Thunnus obesus) fish is one of the large pelagic fish species with the most catches after skipjack fish from all landed fish. The results of the analysis of the relationship between weight weights show that the growth pattern of big eye tuna (Thunnus obesus) is allometric negative (b <3). In fisheries biology, this long-weight relationship of fish is one of the information that needs to be known in terms of fisheries resource management.